CTRP1 Aggravates Cardiac Dysfunction Post Myocardial Infarction by Modulating TLR4 in Macrophages - Gu, Yang; Hu, Xiao; Ge, Pei-Bing; Chen, Yu; Wu, Shen; Zhang, Xi-Wen (Frontiers in Immunology, 2021)
CTRP1 (C1q/TNF-α [tumour necrosis factor-α]-related protein 1), an adiponectin paralogs, is associated with diabetes and adverse events in cardiovascular disease. However, its effect on cardiac function post myocardial infarction (MI) is unclear. Our study aimed to explore the role of CTRP1 in cardiac function post MI. CTRP1 global knockout mice were subjected to left anterior descending ligation to establish the MI model. C57BL6J mice were also administered recombinant CTRP1 protein (200 μg/kg) 7 days post MI. As a result, mice with CTRP1 deficiency exhibited an increased survival rate, a reduced infarct area, improved cardiac function and decreased inflammation and oxidative stress levels at 4 weeks post MI compared with those of mice receiving the CRTP1 injection, whose conditions deteriorated. However, cardiomyocytes with either CTRP1 silencing or CTRP1 treatment showed few differences in inflammation and oxidative stress levels compared with those of the control under hypoxic conditions. The activation of macrophages isolated from CTRP1-deficient mice was decreased in response to interferon-γ, while CTRP1 enhanced the activation of macrophages in response to interferon-γ. Macrophage scavengers and clodronate liposomes antagonized the effects of CTRP1 injection in mice. We also found that CTRP1 regulated macrophage activation via adiponectin receptor 1, which binds to TLR4 on the macrophage membrane. TLR4 knockout also antagonized the effects of the CTRP1 protein on mice with MI. Taken together, these data indicate that CTRP1 supresses cardiac function post MI via TLR4 on macrophages. Targeting CTRP1 may become a promising therapeutic approach to cardiac dysfunction post MI.